Efektivitas Sosialisasi Mitigasi Bencana dalam Meningkatkan Kesiapsiagaan Masyarakat Kota Surabaya - Marinda, Riska Dwi; Muttaqin, Husnul (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This research discusses the effectiveness of the disaster mitigation socialization program implemented by the Regional Disaster Management Agency (BPBD) of Surabaya City in enhancing community preparedness for potential disasters. Surabaya, as a coastal city, has a high risk of disasters, making it crucial to increase community awareness and knowledge. This study aims to assess the effectiveness of the disaster mitigation socialization program implemented by the Regional Disaster Management Agency (BPBD) of Surabaya City in improving community preparedness. The research employs a qualitative method with an evaluative approach. Data is collected through in-depth interviews with BPBD representatives, volunteers, and community members, as well as participatory observation of socialization activities to directly assess the implementation process and its impact. The research results show that the socialization program of the BPBD Surabaya is generally effective in building a community-based preparedness foundation. This success is reflected in the high level of community participation, which not only includes attendance in the training but also follows up with tangible actions such as the preparation of self-evacuation maps and the formation of disaster preparedness groups. Participants' understanding of the material has also improved..